The letters of Lord Nelson to Lady Hamilton with a supplement of interesting letters : in two volumes /: in two volumes. ([2012]) - Viscount, Nelson, Horatio Nelson, 1758-1805; Lady, Hamilton, Emma, 1765-1815
No abstract available